Comparing the quality of life of adults with and without intellectual disability. Issue 4 (25th January 2016) - Simões, C.; Santos, S.
Abstract: Background: Quality of life (QOL) is an important issue for all citizens, comprising equity, equality, inclusion and participation of each person in society. The research purposes driving this investigation were (1) to compare QOL among people with and without intellectual disability (ID) and (2) to examine the predictors of QOL in both groups of participants. Methods: Data were collected from 1929 adults, including 1264 individuals with an ID and the remainder ( n  = 665) were participants without a disability. QOL was assessed by the Portuguese version of the Personal Outcomes Scale. Results: The findings supported significantly higher QOL for adults without ID. Furthermore, QOL is influenced by individual and environmental variables, stressing that the health status was the highest mutual predictor of QOL among those with and without ID. Conclusion: The gaps among both groups of participants should be addressed in service provision and policies. Taking into account the research findings, the personalised supports should enable the full inclusion and participation of adults with ID in community‐based settings.